2018
DOI: 10.1021/acsami.7b14498
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Mat of Poly(vinyl alcohol)/Graphene Oxide for Superior Electrolyte Performance

Abstract: Here, we describe an electrospun mat of poly(vinyl alcohol) (PVA) and graphene oxide (GO) as a novel solid-state electrolyte matrix, which offers better performance retention upon drying after infiltrated with aqueous electrolyte. The PVA-GO mat overcomes the major issue of conventional PVA-based electrolytes, which is the ionic conductivity decay upon drying. After exposure to 45 ± 5% relative humidity at 25 °C for 1 month, its conductivity decay is limited to 38.4%, whereas that of pure PVA mat is as high as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 40 publications
(82 reference statements)
0
29
0
Order By: Relevance
“…[ 28b,29 ] The D and G bands related to the graphitic structures are pronounced for both GO and PVAA–GO, indicating the successful introduction of GO into the GPE. [ 30 ] To demonstrate the crucial function of PAA and GO in improving the water retention and ionic conductivity of the GPE, the water and alkali uptake behaviors of PVA, PVAA, and PVAA–GO were analyzed. Remarkably, as shown in Figure 2h, both the water and alkali uptake capabilities of PVAA and PVAA–GO substantially increase compared to PVA.…”
Section: Figurementioning
confidence: 99%
“…[ 28b,29 ] The D and G bands related to the graphitic structures are pronounced for both GO and PVAA–GO, indicating the successful introduction of GO into the GPE. [ 30 ] To demonstrate the crucial function of PAA and GO in improving the water retention and ionic conductivity of the GPE, the water and alkali uptake behaviors of PVA, PVAA, and PVAA–GO were analyzed. Remarkably, as shown in Figure 2h, both the water and alkali uptake capabilities of PVAA and PVAA–GO substantially increase compared to PVA.…”
Section: Figurementioning
confidence: 99%
“…In our work, we used GO as an additive to the hydrogel electrolyte, first, to solve the key problem of rapid water evaporation and to promote water retention over long time (without packaging), and second, to enhance capacitance and rate performance by improving ionic conductivity. To elucidate the important role of GO on the mechanical and electrochemical performance of our MP‐SMSCs, we also fabricated GO‐free PVA hydrogel electrolyte for comparison, while other steps were kept unchanged.…”
Section: Resultsmentioning
confidence: 99%
“…As demonstrated, the addition of GO led to a significant increase in the area under CV curves of MP‐SMSCs with equal mass loading, suggestive of an enhancement in the cell's areal capacitance from 7.29 to 12.1 mF cm −2 , nearly 66% increase (Figure e). Notably, GO exhibited the positive effects on greater water retention due to the presence of functional groups on its large surface area elucidated by significantly enhanced cycling stability (Figure S1, Supporting Information) . Compared with GO‐free devices, MP‐SMSCs with GO incorporation showed obvious flexibility and resistance to mechanical damage under extreme deformation after long‐time exposure to ambient conditions and freeze‐drying (Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Boron doping of the gel electrolyte composite improved its thermal stability and the authors found that the specific capacitances of gel electrolytes with and withoutG Oa re almost similar (Figure 14 A), the only significant difference in charges torage values evident when the cell was cycled at slow scan rates.T his may be creditedt o the intimate contact betweent he electrodes by the gel electrolyte,b ut using impedance spectroscopy it was found that GO may be exhibiting pseudocapacitance that can contribute to the increased C s . Water retention of GO was studied in thermally crosslinked GO/PVAe lectrospun composites by Pan et al, [90] in which alaser-scribedsupercapacitor was createdb yd rop-casting GO onto the GO/PVA electrospun mat followed by laser ablation to create laser-reduced GO electrodes (Figure 14 B). Water retention of GO was studied in thermally crosslinked GO/PVAe lectrospun composites by Pan et al, [90] in which alaser-scribedsupercapacitor was createdb yd rop-casting GO onto the GO/PVA electrospun mat followed by laser ablation to create laser-reduced GO electrodes (Figure 14 B).…”
Section: Supercapacitorsmentioning
confidence: 99%